ICTs and Public Health in the Context of COVID-19 - Nirupam Bajpai; John Biberman; Yingxin Ye (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
The globe is currently gripped by the deadliest and most widespread pandemic it has faced in over a century. Confronted by accelerating death tolls and widespread fear, societies around the world have also been forced to acknowledge points of stress in their economic and social fabrics that had long gone overlooked. In the midst of this turmoil, Information and Communications Technology (ICT) has played an essential role in facilitating the safe relief and treatment of affected populations. ICT has also shown itself to be essential both to bolstering long-term resiliency against future pandemics and to resolving the secondary challenges that emerge within a socially distanced environment. However, involving ICT in in pandemic relief and prevention carries with it its own set of challenges involving transparency, accountability, and privacy. Governments which apply ICT must ensure that far-reaching crisis measures do not become permanently entrenched in society, and that measures which are taken are deemed fair, proportional and just. In an annex, we summarize the best practices for ICT usage in a pandemic which have emerged during the global COVID-19 response.
Keywords: 330